(untitled) (Journal of Interdisciplinary Insights, 2024)
This study investigates the influence of benchmarking on the quality of teaching within higher education institutions in Mongolia. Benchmarking, defined as the process of comparing an institution’s practices and performance metrics to those of leading organizations, serves as a strategic tool for enhancing educational quality and competitiveness. Utilizing a mixed-methods approach, the research encompasses both quantitative surveys and qualitative interviews with academic staff and administrators. The findings indicate that benchmarking significantly contributes to improvements in teaching methodologies, curriculum development, and administrative efficiency. However, challenges such as cultural resistance and resource constraints were identified as barriers to effective benchmarking implementation. The study concludes with recommendations for optimizing benchmarking practices to better support educational excellence and sustainable growth in higher education institutions.